Faktor-Faktor Yang mempengaruhi Price Earning Ratio (PER) Sebagai Salah Satu Kriteria Keputusan Investasi Pada Perusahaan Manufaktur Yang Terdapat Di Bursa Efek Indonesia - Hari Setiono; Tatas Ridho Nugroho (Program Studi Akuntansi, Fakultas Ekonomi, Universitas Islam Majapahit, 2018)
Price Earning Ratio is a more popular approach in stock analysis because investors assume that price earning ratio is a description of a company's performance. This research uses quantitative method with causal relationship, consist of four variable that is Dividend Payout Ratio, Current Ratio, and Variance of Earning Growth as independent variable and Price Earning Ratio as dependent variable. The purpose of this research is to know the influence of Dividend Payout Ratio, Current Ratio, and Variance of Earning Growth on Price Earning Ratio at manufacturing companies listed on Indonesia Stock Exchange. The population in this study is a manufacturing company in Indonesia Stock Exchange. Sampling technique in this research use purposive sampling method, that is sample determination technique based on certain criterion, hence amount of sample of consumer goods company fulfilling criteria counted 10 company. The data used in this study is secondary data obtained from financial report data for the period 2012-2016 taken from the Indonesia Stock Exchange. This research uses data analysis methods first classical assumption testing before hypothesis testing. Hypothesis test in this research use multiple linear regression with t test and F test. The result of research show that partially only VEG have significant influence on PER, while DPR and CR have no significant effect to PER, this is in accordance with the research result of M. Reeza Pramadika (2011) found that DPR and CR variables did not significantly affect PER, in manufacturing companies (automotive sector) listed on the Indonesia Stock Exchange.